2016
DOI: 10.1007/s00404-016-4012-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of osteogenesis imperfecta type I in pregnancy; a review of literature applied to clinical practice

Abstract: In conclusion, women affected by type I OI represent a subset of patients whose pregnancies should be considered high risk and warrant a multidisciplinary approach in a referral center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 40 publications
0
28
0
1
Order By: Relevance
“…Using this concept, we were able to observe significant increases in DXA follow-up scans (up to 33%), which indicate the ability of the skeleton to recover [42,43]. Besides this described bone-specific approach, pregnant individuals with known monogenic bone disorders (e.g., osteogenesis imperfecta) may furthermore benefit from a multidisciplinary treatment in a referral center in order to also monitor other complications of connective tissue disorders and the fetal well-being [44]. Whether a cesarean section is associated with fewer complications than vaginal delivery remains controversial but needs to be considered and decided on an individual basis.…”
Section: Discussionmentioning
confidence: 97%
“…Using this concept, we were able to observe significant increases in DXA follow-up scans (up to 33%), which indicate the ability of the skeleton to recover [42,43]. Besides this described bone-specific approach, pregnant individuals with known monogenic bone disorders (e.g., osteogenesis imperfecta) may furthermore benefit from a multidisciplinary treatment in a referral center in order to also monitor other complications of connective tissue disorders and the fetal well-being [44]. Whether a cesarean section is associated with fewer complications than vaginal delivery remains controversial but needs to be considered and decided on an individual basis.…”
Section: Discussionmentioning
confidence: 97%
“…Bisphosphonates used routinely by this patient group is contraindicated for the pregnancy as they may cause fetal skeletal anomalies or congenital malformations, and many studies recommend discontinuing them after conception. [2,3] However, these problems may be mitigated by calcium and vitamin D support and keeping weight gain under control. It has been shown that checking the values of calcium, phosphate, vitamin D, parathyroid hormone, LDH, CK, CRP, and kidney and liver function tests by a 3month laboratory analysis would help the management of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Type I is the common one which has a better prognosis. [2] Type II is the most slow-progressing form. Its usual prevalence is up to 6-7 in 100,000 and most of them are new mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Limited information on the maternal skeletal outcome following pregnancy and lactation in women with OI is known; however, fractures and other complications have been reported . Currently, bisphosphonates (BPs) are the most widely prescribed antiresorptive for the treatment of metabolic bone diseases associated with excessive bone resorption .…”
Section: Introductionmentioning
confidence: 99%